2008
DOI: 10.1590/s0102-86502008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the lower spleen pole remaining after subtotal splenectomy in rats

Abstract: PURPOSE: To determine whether the lower pole of the spleen grows after subtotal splenectomy following ligature of major spleen blood vessels. METHODS: Thirty-nine Wistar rats (328.8 ± 27.8 g) submitted to subtotal splenectomy with preservation of the lower splenic pole were divided into two groups: group 1 (control, n=20), immediate removal of the lower pole; group 2 (n=19), removal of the pole on postoperative day 80. The length, width and thickness of the pole were measured. In the control group, mean percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…The same occurred with the width and thickness. These results go against those of a study that shows that the lower pole grows over time 16 .…”
Section: Discussioncontrasting
confidence: 94%
“…The same occurred with the width and thickness. These results go against those of a study that shows that the lower pole grows over time 16 .…”
Section: Discussioncontrasting
confidence: 94%
“…The average inferior pole percentage was greater on postoperative day 80 than on day 10. This suggests that the splenic remnant grew over time, as described by Paulo et al 32 In another partial splenectomy model, growth was also seen in the inferior pole 33 . This is a promising observation, as it suggests that splenic function can improve, and was demonstrated in previous work 5 .…”
Section: Discussionsupporting
confidence: 58%
“…Paulo et al 22 observed the growth of the remaining tissue on the 80 th day. STPI performed in other models than the one described in our work, showed that the histological pattern of this pole becomes similar to normal splenic tissue in 45 dias 23 .…”
Section: Introductionmentioning
confidence: 98%
“…Paulo et al 22 Studies on immunohistochemistry and molecular genetics are being developed to complement this work in order to clarify these issues.…”
mentioning
confidence: 99%